2019
DOI: 10.1016/j.mvr.2019.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

Migration velocity of red blood cells in microchannels

Abstract: The lateral migration of red blood cells (RBCs) in confined channel flows is an important ingredient of microcirculatory hydrodynamics and is involved in the development of a cell free layer near vessel walls and influences the distribution of RBCs in networks. It is also relevant to a number of lab-on-chip applications. This migration is a consequence of their deformability and is due to the combined effects of hydrodynamic wall repulsion and the curvature of the fluid velocity profile. We performed microflui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 68 publications
3
35
0
Order By: Relevance
“…Nonetheless, studies in the literature report that the local hematocrit distribution could be related to the RBC dynamics which is governed by the shear stress experienced by the cells (Lanotte et al, 2016 ; Minetti et al, 2019 ) with respect to their deformability. Therefore, the RBC radial migration may be the result of the interaction between lift force, shear rate gradient and non-linear shear induced diffusion (Grandchamp et al, 2013 ; Losserand et al, 2019 ). The lateral distribution in the parent vessel of the single-mesh network may also result from the design of the inflow channel which leads to an uneven RBC distribution for higher velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies in the literature report that the local hematocrit distribution could be related to the RBC dynamics which is governed by the shear stress experienced by the cells (Lanotte et al, 2016 ; Minetti et al, 2019 ) with respect to their deformability. Therefore, the RBC radial migration may be the result of the interaction between lift force, shear rate gradient and non-linear shear induced diffusion (Grandchamp et al, 2013 ; Losserand et al, 2019 ). The lateral distribution in the parent vessel of the single-mesh network may also result from the design of the inflow channel which leads to an uneven RBC distribution for higher velocities.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies show that in pressure-driven channel flows where non-constant shear (or Simulation. To examine whether the lateral migration of RBCs in our simulation obeys the lift scaling that Coupier et al [46] and Losserand et al [68] proposed for Poiseuille flow, we adopt theoretical shear rates from the asymptotic solution of pressure-driven flow in rectangular channel [56] and calculate the lift velocities applying V l ∼γ/h (abandoning all prefactors for generality). Further with weighted normalisation, we obtain the dimensionless theoretical lifts (V l,y andV l,z ) for both W and H directions ( Fig.…”
Section: 1mentioning
confidence: 99%
“…We showed that when the local density of cells is sufficient, confined flows in the height direction promote the formation of trains, which can be understood from the action of quadrupolar interactions between particles (Janssen et al 2012), which tend to realign and particles and make them reach a preferred inter-particle distance. On the contrary, the formation of lines completely depends on the presence of lateral walls, which make RBCs lift away (Losserand et al 2019). This migration away from the wall has two effects: it increases the local density of RBCs, thus favouring interactions, but also creates preferred positions for RBCs travelling in the channel, depending on the number of RBCs travelling side by side.…”
Section: Discussionmentioning
confidence: 99%
“…In the simulations, the channel width and height are 30 and 8 microns, respectively. In a dilute suspension, the RBCs leave the nearwall region due to the action of a lift force associated with the presence of the wall and the curvature of the velocity profile (Losserand et al 2019). They form a unique line of cells at the mid-width of the channel.…”
Section: Numerical Simulationsmentioning
confidence: 99%